THE DYNAMICS OF INDONESIAN BANKING COMPETITION 2006 – 2013 - Cintya Adita; Charvin Kusuma (Bina Ekonomi, 2015)
There have been many views and hypothesis regarding the impact of competition on banking performances and stability. In order to find the optimum level of competition, we should start by measuring the level of competition in the industry. This article shows the development of competition level in Indonesian banking, measured with four different methods (Concentration ratio, Herfindahl-Hirschmann Index, H-statistic, and Lerner Index). We found that concentration in deposit and loan markets have become slightly more concentrated, with increasing market power indicated by Lerner Index. We also found that Lerner Index of Indonesian banking have a bimodal distribution, which indicates that Indonesian banking tend to be divided into two clusters based on its market power. On the other hand, development of H-statistic illustrates different tendencies where it indicates that banking market power is diminishing. The different result indicates that, even if the overall assets of Indonesian banking have become more productive, it has become more costly for them to earn new assets. Therefore we recommend Indonesian banking to do consolidations in order to gain economies of scale and scope in earning new assets.